Rice Bran Protein Isolates: Preparation and their Physico-Chemical and Functional Properties - Patsanguan, Sirapat; Hisaranusorn, Nattanun; Phongthai, Suphat; Rawdkuen, Saroat (Food and Applied Bioscience Journal, 2017)
Rice bran protein isolates (RBPI) were prepared by two combination extraction techniques; microwave-assisted extraction with homogenization (MAE-H:800 W for 4 sec, 14000 rpm for 10 min) and the ultrasonic-assisted extraction with colloid milled (UAE-C:160W for 5 min, 3000 rpm for 30 min) compared with conventional alkaline extraction (AKE) method before subjected to protein recover by using three-phase partitioning (TPP).RBPI were analyzed for physical, chemical and functional properties. Bulk density and whiteness of RBPI ranged 0.24 to 0.46 g/mL and 83.88 to 88.06, respectively. Lysine and histidine are the major amino acids in RBPI (3017-4877 and 1864-3535 mg/100g). The highest total phenolic content was found in RPBI using AKE (15.89 mg/g), while MAE-H gave the highest content antioxidant activities by FRAP (9.81 x 102mM/g) and DPPH assays (8.83%). The lipid peroxidation of RBPI ranged 11.30 to 19.39%. Nitrogen solubility index of RBPI were 57.84 to 73.12%, while in original rice bran was 18.04%. Water-holding and oil absorption capacity ranged 1.72 to 2.69 g/g, and 1.85 to 3.75 g/g, respectively. The highest foaming capacity was found in RBPI using UAE-C (62.50%), while the lowest was observed in RBPI using MAE-H (54.44%).